2020
DOI: 10.21203/rs.3.rs-135707/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anticoagulation in Patients With a Femoral Neck Fracture: Evaluating Daily Practice.

Abstract: Background: Geriatric hip fracture patients are fragile and mostly suffering from multiple comorbidities, such as cognitive or cardiovascular disease, in which the use of antiplatelet therapy or vitamin K antagonists is common. The aim of this study is to assess the effect of antiplatelet therapy and vitamin K antagonists on perioperative care and patient outcome after hip hemiarthroplasty in daily practice.Methods: Patients with a femoral neck fracture requiring hip hemiarthroplasty were included in the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Van Rijckevorsel et al, have published their observational cohort study, in which they reported an increased incidence of haematomas associated with VKAs compared to antithrombotic agents (29). Overall, the literature supports the view that patients on warfarin are more likely to have a delayed time to surgery (27,28,29). However, delayed surgical treatment is associated with increased post-operative mortality (30,31).…”
Section: Vitamin K Antagonistsmentioning
confidence: 96%
“…Van Rijckevorsel et al, have published their observational cohort study, in which they reported an increased incidence of haematomas associated with VKAs compared to antithrombotic agents (29). Overall, the literature supports the view that patients on warfarin are more likely to have a delayed time to surgery (27,28,29). However, delayed surgical treatment is associated with increased post-operative mortality (30,31).…”
Section: Vitamin K Antagonistsmentioning
confidence: 96%